Amana wanzhensis (Liliaceae), a new species from Anhui, China - Han, Bangxing; Zhang, Ke; Huang, Luqi (Phytotaxa, 2014)
Amana wanzhensis, a new species from Ningguo County, Eastern China, is described and illustrated. A. wanzhensis is similar to A. erythronioides in sharing villous tunics and oblanceolate leaves, but differs from it by having shorter bracts (0.1–0.5 cm long), yellow anthers, and deciduous tepals.